2001
DOI: 10.1016/s1074-7613(01)00228-x
|View full text |Cite
|
Sign up to set email alerts
|

Cr2, a Candidate Gene in the Murine Sle1c Lupus Susceptibility Locus, Encodes a Dysfunctional Protein

Abstract: The major murine systemic lupus erythematosus (SLE) susceptibility locus, Sle1, corresponds to three loci independently affecting loss of tolerance to chromatin in the NZM2410 mouse. The congenic interval corresponding to Sle1c contains Cr2, which encodes complement receptors 1 and 2 (CR1/CR2, CD35/CD21). NZM2410/NZW Cr2 exhibits a single nucleotide polymorphism that introduces a novel glycosylation site, resulting in higher molecular weight proteins. This polymorphism, located in the C3d binding domain, reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
142
2
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 196 publications
(152 citation statements)
references
References 47 publications
(4 reference statements)
7
142
2
1
Order By: Relevance
“…8, C and D) or intermediate (tetramers containing a higher dose of biotinylated anti-sIgM; data not shown) anti-sIgM stimulus was used to crosslink the BCR alone, B cells from both strains responded similarly in the numbers of cells responding and the amplitude of the response. These findings were similar to those demonstrated previously for the parental B6 and B6.Sle1c strains (10). To ensure that the decreased signaling mediated by CD35/CD21 was not due to altered expression of CD35/CD21 on (NZB ϫ B6.Sle1c)F 1 B cells, the binding of mAbs to CD35 (8C12; Fig.…”
Section: Cd35/cd21-mediated Signaling Is Diminished In (Nzb ϫ B6sle1supporting
confidence: 89%
See 4 more Smart Citations
“…8, C and D) or intermediate (tetramers containing a higher dose of biotinylated anti-sIgM; data not shown) anti-sIgM stimulus was used to crosslink the BCR alone, B cells from both strains responded similarly in the numbers of cells responding and the amplitude of the response. These findings were similar to those demonstrated previously for the parental B6 and B6.Sle1c strains (10). To ensure that the decreased signaling mediated by CD35/CD21 was not due to altered expression of CD35/CD21 on (NZB ϫ B6.Sle1c)F 1 B cells, the binding of mAbs to CD35 (8C12; Fig.…”
Section: Cd35/cd21-mediated Signaling Is Diminished In (Nzb ϫ B6sle1supporting
confidence: 89%
“…There are several potential candidate genes for lupus susceptibility in these latter two regions, including a cluster of four novel genes containing fibronectin type III domain fragments and the protein tyrosine phosphatase Ptpn14 (also known as PTP36). We have already identified Cr2 to be a strong candidate gene for lupus susceptibility in the Sle1c interval based on the presence of a single nucleotide polymorphism in the ligand binding domain of CD21, which introduces a novel N-linked glycosylation site and results in decreased binding of C3d ligands and impaired B cell signaling (10). Furthermore, we have found that the NZW complement receptor-related gene Y (Crry), which lies within 10 kb of Cr2 in the Sle1c interval and encodes a potent complement regulatory protein in mice (22), has alterations in its structure and function (S. N. Tchepeleva and S. A. Boackle, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations